The relationship between active learning models in music lessons in elementary schools and multiple intelligence areas - ÇOBAN, SİBEL (ELSEVIER SCIENCE BV, 2011)
The objective of this study is to reveal the effect of the active learning model on the multiple intelligence areas of students when applied in elementary school music classes. The working group of the study consisted of 52 students, 52 students. parents and a music teacher. The study was conducted at an Istanbul elementary school during the first term of the 2010-2011 school year. The experimental group was taught using active learning education techniques. The pre test-post test was performed on students. parents and the music teacher of the school. The study used the Multiple Intelligence Development Assessment Scale, developed by Shearer (1994) and adapted to Turkish by Kaya (2004), with a Personal Information Form and Observation Form. (C) 2011 Published by Elsevier Ltd.
Keywords: Music Education; Active Learning; Multiple Intelligence